The Necessity and Feasibility of the Pledge of Intangible Assets in the Contemporary Legal System of Iran - Muhammad Hasan Sadeghi Moqadam; Hojjatollah Moradi (آموزه‌‌های فقه مدني, 2022)
In article 774 of the civil code following the well-known opinion in fiqh, the void of the pledge of intangible assets has been specified. The important bases of the void of the pledge of intangible assets have been codified the inalienability of the seizure of the pledged intangible assets and the lack of providing trust and the failure of the payment or settlement of the debt. However, all these cases in fiqh have been questioned. In the legal system of Iran, many regulations have been enacted latter to the civil code that they have no consistency with the traditional rules of the pledge. Some of them have excluded the seizure of the pledged intangible assets from the provisions of the validity of the pledge and some others have recognized the definite nontangible assets such as credits and stocks of guarantee are collateralizable. On the other side, the voidance of the pledge of intangible assets makes such assets to some extent go out of the economic cycle of the society and it causes losses in the business cycle and deprives the property’s owner from the complete benefit of his asset. All these factors make an endeavor for knowing intangible assets be necessary. There are five important approaches have been assessed in this paper which are: utilization of agreement with a no-name, utilization of the Agreement of Pledge utilization of transactions with the right of redemption, acceptance of the implied abrogation (implied appeal) of articles 774 and 772 of the civil code and their exclusion of jus cogens (compelling law -peremptory-).